AVALIAÇÃO DO CONSUMO ALIMENTAR DE IDOSOS DA ÁREA UBANA E RURAL DE IJUÍ/RS - Machado, Luciele d. L.; Beier, Liége L.; Rost, Débora; Dallepiane, Loiva B.; Schweigert, Ingrid D.; Battisti, Iara D. E.; Bellé, Tânia R. L. (Salão do Conhecimento, 2013)
Resumo